Cultural effect on online shopping trust - Yeong, Woon Chin (2006)
Online shopping has become the common activity to do in United Kingdom. At the mention of it, one would think of online shopping as averting towards the American culture, since nearly everything in the country is technologically intertwined. Ever since the introduction of the Internet and computers nearly 20 years ago, the Internet marketing industry has been creeping into the fabrics of any parts of the world community. The combination of modern life and modern technology has also changed the way consumers consumed information. It has also made information distribution become more transparent and easily accessible. For that reason, the adoption level in technology may occur in a different way for all kinds of culture in the society, but these changes that occurred are in parallel with the new trends which is visible in the online shopping industry. The aim of this study is to analyze cultural influence in online shopping trust and trend in the area of Nottingham, United Kingdom on some selected characteristics that determine the online shopping trend of different culture and age groups. A questionnaire survey was conducted to collect primary data information for this study. The questionnaire gathered information on age, income, gender and online shopping factors which might determine the shopping trend of 100 judgmentally selected online shopping respondents. Chi square, crosstabs, ANOVA tests were used to estimate the impact of the above characteristics on the online shopping trend. Gender appears to be the most important variable explaining the trend of online shopping among the target population. Other sociodemographic characteristics such as age, income and other online shopping determinant factors were also significant in explaining the online shopping trend in Nottingham. Finally, due to financial limitation on the study, the sample is limited to one city in United Kingdom. Perhaps, the research would have been more thorough if all other areas useful in online shopping were taken into consideration.